As Measured By James Watt: The Ranter & Other Engines. (3rd July 2017) - Lamb, Richard P.H.
Abstract : The importance of the data collected by James Watt in the 1770s while testing the performance of several Newcomen engines cannot be overestimated. These measurements, together with surprisingly accurate laboratory experiments, allowed such parameters as the wastage of steam and the functioning of the condenser to be quantified for the first time. This knowledge and study eventually led to that branch of science now known as thermodynamics.